Influence of Green Supply Chain on Performance of Mining and Extraction Firms in Kenya - Otieno, James; Kitheka, Samson; Hood, Anwar; Egessa, Mathew (International Journal of Supply Chain Management, 2025)
Purpose: The performance of mining and extraction firms in Kenya have been below par. The industry recorded a decline in production of most of the minerals such as titanium and soda ash and a declining trend towards contribution to the gross domestic product. This study sought to examine the influence of green supply chain on the performance of mining and extraction firms in Kenya. Methodology: The research employed a descriptive design and targeted a sample of 201 respondents from registered mining and extraction firms in Kenya. The study used stratified random sampling techniques for respondent selection. Data were gathered using structured questionnaires. Pilot study was carried out to determine the reliability and validity of the research instrument. Statistical package for social sciences version 27 was used to analyze the data. Descriptive, correlation and regression statistics were used to evaluate the relationship between green supply chain and firm performance. Findings: The study found that green supply chain have a statistically significant and positive effect on firm performance. These practices were associated with reduced operational costs, enhanced regulatory compliance, improved stakeholder relationships, and greater environmental responsibility. The regression analysis confirmed a strong positive correlation between green supply chain adoption and improved organizational outcomes. Unique Contribution to Theory, Practice, and Policy: The study extends the application of the Natural Resource-Based View (NRBV) by empirically validating the strategic value of green supply chain management practices in the mining and extraction sector, a context that has been underexplored in sustainability literature. The findings provide actionable insights for industry practitioners on how adopting green supply chain strategies can yield operational and competitive benefits, including efficiency gains and enhanced market reputation. The study underscores the need for supportive regulatory frameworks and targeted capacity-building initiatives to foster broader adoption of green supply chain practices in Kenya's mining sector. It advocates for policy instruments that incentivize eco-innovation, stakeholder engagement, and long-term environmental stewardship.